Narrating Recruitment Model for Legislator Candidates: Is It Fair? - Mutawalli Mukhlis, Muhammad; Maskun, Maskun; Budiyanto, Budiyanto; Jumas, Jumas; Rahadian, Dian; Olemanu Lohalo, Georges (Faculty of Law, Jambi University, 2024)
This research analyzes the problems of democratic and aspirational recruitment models and mechanisms for legislative candidates by political parties, aiming at formulating cadre-based recruitment arrangements that best represent democratic ideals. Using normative legal, conceptual, statutory and comparative approaches, this article argues that there are two principal recruitment problems. First, legal arrangement pertaining to methods, procedures, and requirements for the recruitment is generally absent from the statutory regulations. Second, the internal process of decision-making within the political party is generally undemocratic, owing partly to the pragmatism and power-oriented calculation of the elites within the party. Recommendation for ideal recruitment arrangements is thus proposed to ameliorate these problems. Among others, the recruitment by political parties must consider aspects of representativeness, ideological consistency, internal political party flow, development of career path-based cadre systems, and quota fulfillment. Additionally, political party cadre needs training to boost their skills in carrying out main duties and functions as a member of the Board People's Representatives